Vibrational spectroscopic and structural investigations of bioactive molecule Glycyl-Tyrosine (Gly-Tyr) - Çelik, Sefa; Özel, Ayşen E.; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2017)
This study investigated the conformational behavior of biological active molecule Glycyl-Tyrosine (Gly-Tyr) dipeptide and its dimers, by Boltzmann jump and DET calculations. The energy calculations on Gly-Tyr dipeptide as a function of side chain torsion angles enabled us to determine the preferred conformations. The most stable conformations obtained from the above process were further optimized by the DFT calculations. The geometry optimization and vibrational wavenumbers calculations of Gly-Tyr dipeptide were carried out with the Gaussian03 program by using density functional theory (DFF) with B3LYP functional and 6-31++G (d,p) basis set. The dimeric forms of the dipeptide were also formed and energetically preferred conformations of dimers were investigated using the same method and the same basis set. The results provided a good account of the role of the number and type of inter- or/and intramolecular H-bond interactions existing in the dialer and monomer forms of the dipeptides. The fundamental vibrational wavenumbers, IR and Raman intensities for the optimized structure of monomeric and dimeric forms of the dipeptide were calculated and compared with the experimental vibrational spectra of solid Gly-Tyr dipeptide. Vibrational assignment of the molecule was done using the potential energy distribution analysis. HOMO-LUMO energy has been used to elucidate the reasons for intra molecular charge transfer. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: FTIR; Raman; Glycine; Tyrosine; Density functional theory; Density-Functional Theory; Transform Infrared-Spectroscopy; Ab-Initio; Raman-Spectra; Model Compounds; Force-Fields; P-Cresol; Dipeptides; Derivatives; Program